GENDER INEQUALITY IN FATIMA MERNISSI'S NOVEL DREAMS OF TRESPASS (1994): A SOCIALIST FEMINIST APPROACH - UTOMO, WAHYU (2011)
This study is aimed to show the gender inequality in Dream of Trespass novel by using socialist feminism approach. It is done by establishing two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the gender inequality based on the socialist feminism approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is the Dream of Trespass novel written by Fatima Mernisssi in 1994. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis indicated that each of narrative elements of novel have been related into solid unity. Secondly, the novel illustrates six types of inequality for women, namely: social, economic, religious, political, educational and law of gender inequality. Thirdly, the novel represents a criticism of different inequality experienced by women and that women should struggle in order to get their rights.